Aging induced loss of complexity and dedifferentiation: consequences for coordination dynamics within and between brain, muscular and behavioral levels - Sleimen-Malkoun, Rita; Temprado, Jean-Jacques; Hong, S. Lee (Frontiers in Aging Neuroscience, 2014)
Growing evidence demonstrates that aging not only leads to structural and functional alterations of individual components of the neuro-musculo-skeletal system (NMSS) but also results in a systemic re-organization of interactions within and between the different levels and functional domains. Understanding the principles that drive the dynamics of these re-organizations is an important challenge for aging research. The present Hypothesis and Theory paper is a contribution in this direction. We propose that age-related declines in brain and behavior that have been characterized in the literature as dedifferentiation and the loss of complexity are: i) synonymous, and ii) integrated. We argue that a causal link between the aforementioned phenomena exists, evident in the dynamic changes occurring in the aging NMSS. Through models and methods provided by a dynamical systems approach to coordination processes in complex living systems, we: i) formalize operational hypotheses about the general principles of changes in cross-level and cross-domain interactions during aging; and ii) develop a theory of the aging neuro-musculo-skeletal system based on the combination of the frameworks of coordination dynamics, dedifferentiation, and loss of complexity. Finally, we provide operational predictions in the study of aging at neural, muscular, and behavioral levels, which lead to testable hypotheses and an experimental agenda to explore the link between coordination dynamics, loss of complexity and dedifferentiation within and between these different levels.